EFISIENSI LUASAN KUBAH PANEL GALVALUM UNTUK MASJID DI PEDESAAN - Kapindro Hari Sasmita; Wakyudi Wakyudi (ITB Ahmad Dahlan Jakarta, 2021)
The application of dome on mosque buildings is rationally based on the need for recognizable identity (Fithri, Athaillah, and Karsono, 2016). In modern time, mosques in Indonesia look to emphasize the character of domes by variation of curves, details, motives and colors. One of the most popular technologies now to allow the variations is Galvalum Panel, the dome arranged by modular panels made of metal containing zinc and aluminum. It is also stainless and light weight. The modular panels arranged on pipes hollow structures. The challenge for applying the technology is its unaffordable price, especially for mosque developers in villages. This research is aimed to formulate efficiency for applying the technology related to its dimension and budget, especially for people in village. The research method is started from interviewing some suppliers about dimension and unit price standards; then analyzing efficiency of main room area as basis structure for the dome; then calculating surface area of domes in many variations of diameter and height; and the last is multiplying each number of areas by unit price. The result is the most efficient diameter of dome applied in village areas is not more than 5 meters based on analyzed minimum capacity in the main room to accommodate minimum Friday worshipers. Meanwhile the efficient surface area is ranging from 9.48m2 to 57.84m2.